Waste recycling of coal fly ash for design of highly porous whisker-structured mullite ceramic membranes. Issue 16 (December 2019) - Fu, Mao; Liu, Jing; Dong, Xinfa; Zhu, Li; Dong, Yingchao; Hampshire, Stuart
Abstract: Coal fly ash, a solid state waste massively produced from coal combustion, is considered to be highly hazardous to the environment due to its persistently toxic trace elements. High-value added waste recycling is a promising technique to address this issue. In this work, a waste-to-resource strategy is proposed for design of highly porous whisker-structured mullite ceramic membranes derived from waste coal fly ash and Al(OH)3 as raw materials and MoO3 as a single sintering additive. These were characterized in terms of their dynamic sintering behavior, shrinkage, bulk density, porosity, phase evolution, microstructure, pore size distribution, N2 permeation flux, and mechanical strength. Addition of molybdenum trioxide effectively inhibited the sintering densification of membranes while at the same time forming a metastable low viscosity liquid at lower temperatures. This enables formation of a novel and more highly porous whisker-interlocked structure and accelerates the growth of mullite whiskers with controllable morphologies. Without degradation of mechanical properties, the open porosity increased significantly from 41.65 ± 0.13% to 58.14 ± 0.15% with increasing MoO3 content from 0 to 20 wt.% without any pore-forming agent, while shrinkage and pore size decreased. The method proposed in this study is expected not only to give a new and facile insight for high-value added recycling of waste coal fly ash but also to fabricate low-cost high performance ceramic membranes with novel structures for further environmental applications.